2015
DOI: 10.1155/2015/827608
|View full text |Cite
|
Sign up to set email alerts
|

Combination Trimodality Therapy Using Vismodegib for Basal Cell Carcinoma of the Face

Abstract: Background. For large basal cell carcinomas (BCCs) of the head and neck, definitive surgery often requires extensive resection and reconstruction that may result in prolonged recovery and limited cosmesis. Vismodegib, a small-molecule inhibitor of the hedgehog pathway, is approved for advanced and metastatic BCCs. We present a case of advanced BCC treated with combination of vismodegib, radiotherapy, and local excision resulting in excellent response and cosmesis. Case Presentation. A 64-year-old gentleman pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 14 publications
0
14
0
1
Order By: Relevance
“…Studies have revealed that blocking SMO with vismodegib can effectively reduce cellular proliferation [ 130 , 229 ] and inhibit the tumor growth of TAM-resistant xenografts in mice [ 130 ]. Vismodegib is a well-tolerated drug that offers an excellent outcome in canonical HH signaling-dependent cancers, e.g., basal cell carcinoma [ 228 , 230 ]. The limitation of SMO antagonists relates to the activation of the GLI factors independently of SMO in certain cancers [ 231 ].…”
Section: Clinical Use Of Tam In Combination With Other Agentsmentioning
confidence: 99%
“…Studies have revealed that blocking SMO with vismodegib can effectively reduce cellular proliferation [ 130 , 229 ] and inhibit the tumor growth of TAM-resistant xenografts in mice [ 130 ]. Vismodegib is a well-tolerated drug that offers an excellent outcome in canonical HH signaling-dependent cancers, e.g., basal cell carcinoma [ 228 , 230 ]. The limitation of SMO antagonists relates to the activation of the GLI factors independently of SMO in certain cancers [ 231 ].…”
Section: Clinical Use Of Tam In Combination With Other Agentsmentioning
confidence: 99%
“…To date, there is no evidence to suggest systemic chemotherapy improves local control outcomes when combined with RT for advanced BCC. In 2012, vismodegib became the first systemic therapy approved for BCC ( 5 ), followed by sonidegib approval in 2015, and evidence continues to be generated as combination with RT is explored in advanced, unresectable cases ( 10 , 11 ). In our patient with multifocal BCC, all lesions exhibited some response to vismodegib, with complete and durable responses noted in those larger lesions treated with combination therapy and a durable complete clinical response in the right lateral ankle lesion with vismodegib alone, a remarkable finding.…”
Section: Discussionmentioning
confidence: 99%
“…These trials suggest that this drug may provide a viable option for the treatment of previously untreatable BCC without risk of a potentially disfiguring surgery. Recent studies suggest a combination therapy with radiation and vismodegib could be even more effective for the treatment of advanced disease [ 10 ]. However, in our case, consideration should be given to all potential treatment options, accounting for the overall health of patient and after a detailed discussion of risks and benefits of each treatment approach.…”
Section: Discussionmentioning
confidence: 99%